Process Modeling and Techno-Economic Analysis of Xylitol Production from Oil Palm Empty Fruit Bunch (OPEFB) using SuperPro Designer® - Salam, Wildan Qoharisma; Pramanda, Ihsan Tria; Harjanto, Fariz Hutama Putra; Rukmana, Jaka (Indonesian Journal of Life Sciences, 2023)
The utilization of OPEFB as a biomass waste from the crude palm oil industry offers a potential avenue for producing xylitol through biotechnological processes. The production of xylitol involves a series of steps, including hydrolysis, fermentation, and purification. Xylitol, a sugar alcohol used as a food sweetener, is obtained in crystalline form. However, the fermentation process generates impurities that need to be separated to achieve a high purity level of xylitol. To address this, a combined approach of membrane distillation and cooling batch crystallization was employed in this study. The feasibility of establishing a xylitol production plant was assessed through simulation and techno-economic analysis using SuperPro Designer software version 12. The plant was designed to produce 3.00 MT/batch of xylitol as the primary product, requiring 20 MT/batch of OPEFB. Each batch operation lasted for seven days, with a batch cycle occurring every three days. The simulation was evaluated based on the annual operating cost (AOC). The project incurred a total investment of $2.00 MM, with an annual operating cost of $3.78 MM, and generated yearly revenues of $6.84 MM. The economic analysis revealed that the plant was economically viable, with a payback period of 11 months, a gross margin of 44.71%, and an internal rate of return (IRR) of 62.26%.